Physics of the Solar Corona An Introduction with Problems and Solutions - Aschwanden, Markus (Astronomy and Planetary Sciences,, 2005)
Solar science has evolved rapidly over the past ten years as the results of a new generation of solar space missions have become available. This book provides a thorough introduction to the subject of solar physics, based on those spacecraft observations. The author introduces the solar corona, which has a temperature of several million degrees, and sets it in the context of basic plasma physics before moving on to discuss plasma instabilities and plasma heating processes. The latest results on coronal heating and radiation,which are fundamental processes in all stars, are presented. Spectacular phenomena such as solar flares and coronal mass ejections are described in detail, together with their potential effects on the Earth. The author draws together observations made at many wavelengths from hard X-rays, soft X-rays, extreme UV and radio wavelengths. This paperback study edition of Markus Aschwanden's highly acclaimed PHYSICS OF THE SOLAR CORONA will include 50 pages of problems and solutions which will much enhance the value of the book to students.